Distinct Resistomes and Microbial Communities of Soils, Wastewater Treatment Plants and Households Suggest Development of Antibiotic Resistances Due to Distinct Environmental Conditions in Each Environment - Laura Schages; Florian Wichern; Stefan Geisen; Rainer Kalscheuer; Dirk Bockmühl (Antibiotics, 2021)
The use of antibiotics in humans and animals results in a release of excess antibiotic residues into the environment through wastewaters and insufficient removal in wastewater treatment plants (WWTP), leading to increasing numbers of bacteria enriched in antibiotic resistance genes (ARG). However, the potential transfer of ARG and their host bacteria between different environments remains largely unexplored. Since many factors need to be fulfilled for a transfer between different environments, we hypothesized that antibiotic resistance (ABR) is less frequently transferred between environments in the same geographical region but rather develops and clusters in each distinct environment, leading to characteristic metagenome patterns in samples of different environments. We sampled agricultural soils, a WWTP and private households and performed metagenomic analyses to evaluate differences and potential overlaps in bacterial communities and resistomes of different environments. Wastewater revealed significantly higher richness of ARG (n = 40) and mobile genetic elements (n = 52) than soil and household samples. Bacterial communities differed between the environments and antibiotic resistance factors clustered distinctly. Overall, only few overlaps of ARG between the environments were observed, leading to the conclusion that ABR predominantly develops in individual environments as caused by environmental filtering for ARG, while a transfer between different environments is less likely.